Laser‐Induced Graphene Composites for Printed, Stretchable, and Wearable Electronics. Issue 8 (20th May 2019) - Tehrani, Farshad; Beltrán‐Gastélum, Mara; Sheth, Karan; Karajic, Aleksandar; Yin, Lu; Kumar, Rajan; Soto, Fernando; Kim, Jayoung; Wang, Joshua; Barton, Shemaiah; Mueller, Michelle; Wang, Joseph
Abstract: Graphene‐based composites have received attention as part of the drive towards next‐generation electronic and energy‐storage technologies. However, current graphene synthesis methods are limited by complex, time‐consuming, toxic, costly, and/or often low‐yield procedures. The synthesis of a novel stretchable graphene‐polyurethane‐poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate ink aimed at printing wearable electronics is reported. The procedure is based on low‐cost high‐yield production of high‐performance graphene ink produced by laser induction of polyimide film followed by harvesting the graphene. Screen printing is used to fabricate flexible and intrinsically stretchable micro‐supercapacitors (S‐MSCs) printed on different substrates. The resulting graphene‐based printed S‐MSCs display a remarkably high capacitive performance and attractive mechanical resiliency. High specific areal capacitance, above 23 mF cm −2, is achieved, which is the highest areal capacitance reported for highly stretchable, printed graphene supercapacitors. A repeated (200 cycles) stretchability beyond 100% is obtained while maintaining more than 85% of the S‐MSCs' original capacitance. This unique and highly scalable graphene ink synthesis method holds considerable promise for application in low‐cost graphene‐based chemical formulation, especially in the field of printed and wearable electronics toward multifunctional, energy‐storage systems capable of withstanding severe mechanical deformation while maintaining their optimal electrochemical performance. Abstract : A facile and scalable method for fabricating highly efficient stretchable printed micro‐supercapacitors, based on laser‐induced graphene composites, is described. The good mechanical and electrochemical performance of the printed electrodes and their low materials‐preparation and device‐fabrication costs make them promising for wearable electronics.